Histological changes in the joint tissues of rabbits with gonarthrosis - I. M. Gorkava; M. O. Malyuk; M. A. Kulida; V. V. Klymchuk; O. V. Onyshchenko; V. V. Gonchar; D. O. Kovalenko; D. V. Tarnavskyi (Regulatory Mechanisms in Biosystems, 2025)
Osteoarthritis is a chronic degenerative disease that is accompanied by a progressive degeneration of the articular cartilage, remodeling of the subchondral bone, development of a chronic inflammation of the synovial sheath, and damage to the ligamentous apparatus. In this study, we analyzed the histological changes in the main structures of the ankle joint of the rabbits ( Oryctolagus cuniculus domesticus Linnaeus, 1758, Leporidae), namely: joint cartilage, subchondral bone, synovial sheath, ligamentous apparatus, and menisci on days 7, 14, 21, 28, and 35 after experimentally modeling osteoarthritis. To model the experimental osteoarthritis, we chose the method of intra-articular injection of 4% solution of retinyl acetate and kojic acid (Yellow peel, Medicare, Germany) in a dose of 0.7 mL. The intra-articular injections were performed twice using 23G needles (0.6 * 32 mm) with a seven-day interval. In the earlier stages of development of the pathological state (day 7 of the study), we observed the beginning of degeneration of the joint cartilage, with a local decrease in proteoglycans, which are an important component of the intercellular material of the connective tissue. Furthermore, we detected a slight thickening of the areas of the subchondral bone and a moderate inflammatory infiltration of the joint’s synovial sheath. On day 14 of the studies, we observed a progressing thinning of the articular cartilage with a disturbance of the structure of chondrocytes, osteosclerosis of the subchondral bone, and an active angiogenesis in the synovial sheath. On day 21 of the study of the pathological changes, we observed deep fissures in the cartilage, the development of osteophytes, and an enlargement of the cavities in the subchondral bone, whereas the synovial sheath was undergoing a chronic form of the inflammation processes with fibrotic changes. On day 28, we observed an almost complete breakdown of the joint cartilage, significant osteosclerosis, a notable formation of osteophytes, and total fibrotic changes in the regions of synovial sheath of the affected ankle joint. Additionally, we decided to conduct studies on day 35 to gain an understanding of the further course of the pathology. In this period, we found that the osteosclerosis pathogenesis in the rabbits follo w ing the use of the indicated drug happened unevenly. The obtained results confirmed the dynamic and systemic character of degenerative-inflammatory processes in the ankle joint of the rabbits with induced osteoarthritis. This study offers insights into the pathogenesis of osteoarthritis and can contribute to the development of effective therapeutic approaches.